2012
DOI: 10.5194/nhess-12-1159-2012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing precipitation distribution impacts on droughts on the island of Crete

Abstract: Abstract. Precipitation records from 56 stations on the island of Crete (Greece) revealed that areal mean annual precipitation is of a strong orographic type and its magnitude decreases in west-east direction by as much as 400 mm on average. Amongst many parameters that influence precipitation, the elevation and longitude were the most important and provided the highest spatial correlation. It was found that during the year with minimum precipitation, the precipitation shortage was greater at high elevations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…However, precipitation constitutes the critical factor in the occurrence of drought and, therefore, allows for a better understanding of the process by which drought occurs (Vrochidou and Tsanis 2012). The present study only considered precipitation in the characterization of seasonal droughts.…”
Section: Discussionmentioning
confidence: 99%
“…However, precipitation constitutes the critical factor in the occurrence of drought and, therefore, allows for a better understanding of the process by which drought occurs (Vrochidou and Tsanis 2012). The present study only considered precipitation in the characterization of seasonal droughts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, atmospheric numerical models have been found to be useful in assessing precipitation in areas where observations are scarce and estimates are difficult (Maussion et al, 2011). As shown by several authors in multi-year studies, precipitation and flow patterns found on the island of Crete (Greece) have a strong correlation with the island topography (Kotroni et al, 2001;Koletsis et al, 2009Koletsis et al, , 2010Vrochidou and Tsanis, 2012). This connection was found to be an important clue for spatial drought patterns.…”
Section: Introductionmentioning
confidence: 85%
“…In this work the Weather Research and Forecasting Advance Research (WRF-ARW) model version 3.3 (Skamarock et al, 2008) was used. Initial and lateral boundary conditions from GFS analyses (NCEP, 2003) were provided to the model at six-hour intervals.…”
Section: Methods and Datamentioning
confidence: 99%
“…In this respect, our preliminary findings highlight the capacity of Z. abelicea to cope with increasing summer drought conditions. However, these results call for more investigations as (i) they were only derived from one population from the mountains of western Crete and should be replicated to other mountain ranges on Crete; (ii) the absence of reaction of Z. abelicea towards current climate changes could come from the larger amounts of annual precipitation that fall in the Cretan mountains (N1500 mm/yr) as opposed to the lowlands (b 300 mm/yr) (NOA, 2016;Rackham and Moody, 1996;Vrochidou and Tsanis, 2012); (iii) the cessation of the exploitation of Z. abelicea trees for wood and fodder in the mountains of Crete since the 1960s and the co-occurring climate change may influence and counteract the climatic signal contained in the tree-rings; (iv) although tree growth does not seem to be influenced by changing climatic conditions, the increased drought conditions may affect negatively forest regeneration by lowering seed germination rates and seedling or sapling survival.…”
Section: Stability Of Climatic Sensitivity Through Timementioning
confidence: 99%